Pemerolehan Kosa Kata Anak Suku Jawa Berdasarkan Tempat Tinggal Multilingual - Bambang Prastio (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2017)
ABSTRACT The acquisition of language can not be realized this happens naturally that takes place in a child's brain. Processes when the child is acquiring a language consists of two aspects: the first aspect of performance that consists of aspects of understanding and delivery. Both aspects of competence (linguistic ability). The linguistic ability of the child consists of three components, namely: phonological ability, semantics and sentences. The acquisition of this language is also commonly divided into the acquisition of syntax and semantic acquisition. Semantic acquisition is the acquisition of lexicon or vocabulary. This study aims to analyze the acquisition of language on the semantic level where the child's residence is multilingual, in children aged 2-5 years in kos-kosan western region west, klojen district, Malang, East Java. To obtain accurate results, the need for accurate research methods as well. This study uses a qualitative method. The data in this research were collected using observation method with recording technique and recorded then analyzed by collecting data through observation and recording of conversation conducted by children of Java 2-5 years into field note then describing data result and concluding data analysis result. Keywords: language acquisition, semantic extraction, multilingual